2014
DOI: 10.1177/0961203314526292
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of kidney injury molecule-1 (Kim-1) in patients with lupus nephritis

Abstract: These data suggest the potential use of the u-Kim-1 levels to screen for active LN and for the estimation of t-Kim-1 expression in renal biopsies to predict renal damage, ongoing glomerular nephritis and tubulointerstitial inflammation, and tubular atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 29 publications
10
39
1
Order By: Relevance
“…This rapid effect on kidney function was accompanied by upregulation in expression of lipocalin-2 and kidney injury molecule 1 (kim-1) ( Fig. 3K, L), markers of tubular kidney damage, also observed in lupus nephritis [40][41][42] . Despite the transient nature of proteinuria, expression of these kidney injury markers persisted up to day 6 ( Fig.…”
Section: Skin Exposure To Uv Light Causes Rapid But Reversible Kidneymentioning
confidence: 74%
“…This rapid effect on kidney function was accompanied by upregulation in expression of lipocalin-2 and kidney injury molecule 1 (kim-1) ( Fig. 3K, L), markers of tubular kidney damage, also observed in lupus nephritis [40][41][42] . Despite the transient nature of proteinuria, expression of these kidney injury markers persisted up to day 6 ( Fig.…”
Section: Skin Exposure To Uv Light Causes Rapid But Reversible Kidneymentioning
confidence: 74%
“…Previous studies focused mostly on the diagnostic value of KIM-1, particularly the diagnostic value of urinary KIM-1, in AKI. A few studies detected KIM-1 expression and suggested that it may be related to individual chronic kidney diseases, such as IgA nephropathy, lupus nephritis, or limited cases of type-1 diabetes [19, 20, 16]. Our cross-sectional study recruited patients with kidney diseases of various aetiologies, indicating that both plasma and urinary KIM-1 levels were significantly elevated in both AKI and CKD patients, thereby revealing that KIM-1 expression was also closely associated with chronic kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies showed similar data in biopsies of patients with acute tubular necrosis and demonstrated that increased concentration of KIM‐1 can also be detected in the urine with a high specificity for acute proximal tubular necrosis as soon as 24 h after the insult . Additionally, KIM‐1 is increased in patients with chronic kidney disease and active lupus nephritis . The monocyte chemoattractant protein‐1 (MCP‐1) is a key regulator of the immune system as a potent chemotactic factor for monocytes/macrophages .…”
Section: Introductionmentioning
confidence: 83%